St. Kitts and Nevis : National Environmental Action Plan ([s.n.] [S.l.], 1994)
Analyses the environmental issues affecting St. Kitts and Nevis in a comprehensive, multi-sectoral framework. Sets forth a long-term strategy for maintaining the country's natural environment, the health and safety of its population, and its cultural heritage as economic development occurs.
DC